2010
DOI: 10.1038/ijo.2009.279
|View full text |Cite
|
Sign up to set email alerts
|

Association between single-slice measurements of visceral and abdominal subcutaneous adipose tissue with volumetric measurements: the Framingham Heart Study

Abstract: Objective: Volumetric visceral abdominal adipose tissue (VAT) and subcutaneous abdominal adipose tissue (SAT) as measured by computed tomography (CT) are associated with metabolic risk factors. We sought to identify the correlations of VAT and SAT between area-based measures at different anatomic locations with volumetric measurements to identify the optimal anatomic site, and to relate measurements at this site with metabolic risk factors. Methods: We measured SAT and VAT volumes across the total imaging volu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
146
0
6

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 173 publications
(162 citation statements)
references
References 15 publications
(14 reference statements)
10
146
0
6
Order By: Relevance
“…Shen et al (2007) found that VAT measurement areas located 5-10 cm above L4-L5 have higher correlations with CVD risk factors than the VAT area at the traditional L4-L5 level after adjusting for age, race, and menopausal status. Recent findings by Irlbeck et al (2010) also indicated that single-slice image area measurements of the VAT at L2-L3 and L3-L4 (e.g., 2-6 cm above L4-L5) had strong associations with CVD risk factors in men in a cross-sectional study. We would recommend that, if only a small number of images or a single-slice image is to be analyzed, the image should be taken 5-10 cm above L4-L5, rather than at L4-L5 to best evaluate CVD risk factors.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Shen et al (2007) found that VAT measurement areas located 5-10 cm above L4-L5 have higher correlations with CVD risk factors than the VAT area at the traditional L4-L5 level after adjusting for age, race, and menopausal status. Recent findings by Irlbeck et al (2010) also indicated that single-slice image area measurements of the VAT at L2-L3 and L3-L4 (e.g., 2-6 cm above L4-L5) had strong associations with CVD risk factors in men in a cross-sectional study. We would recommend that, if only a small number of images or a single-slice image is to be analyzed, the image should be taken 5-10 cm above L4-L5, rather than at L4-L5 to best evaluate CVD risk factors.…”
Section: Discussionmentioning
confidence: 86%
“…However, recent studies of Caucasian (Kuk et al 2006), White and African-American cohorts (Demerath et al 2007b) have indicated that the commonly used L4-L5 image site may not be the best location to estimate the VAT volume, whereas the findings for Asian people remain unclear. Furthermore, it is suggested that L4-L5 may not be an appropriate site for investigating the association between VAT and CVD risk factors (Kvist et al 1988;Abate et al 1997;Kuk et al 2006;Demerath et al 2007a;Shen et al 2007;Irlbeck et al 2010).…”
mentioning
confidence: 99%
“…Using a single CT-slice at the level of L3/L4 of the lumbar spine, SAT area and VAT area were measured, according to the method described by Irlbeck et al 15 The muscular abdominal wall was manually traced in order to separate VAT from SAT as the regions of interest. By adjusting the display settings to a window width of À195 to À45 Hounsfield units, the area of adipose tissue could selectively be measured (ImageJ v1.42q, developed by the NIH).…”
Section: Quantification Of Subcutaneous and Visceral Fat Depotsmentioning
confidence: 99%
“…Ис-следования ВЖТ на данном уровне показывают максимальную воспроизводимость и высокую точ-ность измерений. В ряде работ [29,30] показано, что оценка ВЖТ на 5-6 см выше L4-L5 является более точной при проведении МРТ и КТ в динамике.…”
Section: компьютерная томография (кт) и магнитно-резонансная томографunclassified